Human Potential of the Constitutions of the Russian Federation and the People’s Republic of China - G. Chebotarev (BRICS Law Journal)
The article describes the issues of preserving and strengthening traditional cultural, spiritual and moral values implemented in the constitutions of BRICS countries on the cases of Russia and China. Russian Constitution with its amendments of 2020 aims at constitutionalizing cultural and moral values, implementing them to the current legislation, and creating economic, political and social conditions for their enforcement. Also, the article examines the activities of non-governmental organizations in the People’s Republic of China with the focus on their contribution to preservation and amplification of cultural and moral values enshrined in the Constitution of China.